Resor Pantai Ogis Muara Bono Di Pelalawan Dengan Pendekatan Arsitektur Pesisir - Windy Nurjana; Ratna Amanati; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pelalawan has several attractions, and Bono Waves in Ogis Beach Village Teluk Meranti Sub-district is one of them. However, these attractions are not supported by sufficient facilities, one of which is a residential resort. This design has a close connection with the resort destination in Ogis Beach that is with Coastal Architecture Approach. In addition, the design of tourist attraction area Ogis Beach Beach Bono will apply the concept of "Rhythmic Rising Waves" which is the main basic concept in the design. In this concept there are several applications of the design of the nature of waves, such as masses and roofs adapted from the nature of waves that have a low rhyming high. The color of the building is adapted from the color of the kampar river like the color of wood is brown. Then the circulation in the building that is created does not have a partition, so it can surprise people who see it. This design has a design that applies the principle of coastal architecture and the concept taken from the nature of the waves. By using some application of the concept, this design can minimize the negative influence gained from coastal tourism area ogis estuary bono. So this design provides benefits, both environmentally and to the design on the building itself.Keywords: Seaside Resort Ogis Muara Bono in Pelalawan with the Approach Coastal Architecture.